Hydroalcoholic extract of jabuticaba peel in the diet of betta fish - Gesyane Bentos França; Mayara Schueroff Siqueira; Jean Carlos de Souza Melo; Danusia Tavares de Albuquerque; Francine Perri Venturini; Claucia Aparecida Honorato (Boletim do Instituto de Pesca)
The objective of this study was to evaluate the effects of hydroalcoholic jabuticaba bark on the diets of female blue Betta splendens in relation to the level of digestive enzymes, liver metabolism, and antioxidant activity. The sample constituted 150 individuals subdivided into five groups in triplicate, totaling 10 fish per 20 L experimental unit. Commercial diets (40.88% CP and 4374.8 Kcal kg-1) were added to jabuticaba bark (EJB) hydroalcoholic extract concentrations of 0.5, 1.0, 1.5, and 2.0 g .kg-1. The rations were provided twice a day, until apparent satiety, for 21 days. Fish mortality was not observed during the trial. Growth indices did not show any significant differences, apart from feed conversion. The use of the extract promoted an increase in the luminosity of the fish; however, there was no statistical difference in chromaticity a * and b *. A decrease in the activity of Superoxide dismutase (SOD) on the skin of fish fed diets of 1.5 and 2.0g.kg-1 EJB was observed in comparison to the other diets. There was no change in CAT activity. It is concluded that the use of 2 g kg-1 EJB has an antioxidant effect that reflects the greater luminosity of blue female Betta splendens.